Let's go through the steps provided to solve the equation \( 3x + 2b = 6c \) for \( x \):
-
Start with the equation:
\( 3x + 2b = 6c \) -
Step 1: Subtract \( 2b \) from both sides:
\( 3x + 2b - 2b = 6c - 2b \)
This simplifies to:
\( 3x = 6c - 2b \) -
Step 2: This is already done in Step 1, so we have:
\( 3x = 6c - 2b \) -
Step 3: Divide both sides by \( 3 \):
\( \frac{3x}{3} = \frac{6c - 2b}{3} \)
This simplifies to:
\( x = \frac{6c - 2b}{3} \) -
Step 4: Further simplify:
\( x = \frac{6c}{3} - \frac{2b}{3} \)
This simplifies to:
\( x = 2c - \frac{2b}{3} \)
The correct final answer is:
\[ x = 2c - \frac{2b}{3} \]
Now, comparing this with the provided statements:
- The statement "The process has an error. The correct answer is x=2c−23b" is correct.
Thus, the correct response is:
The process has an error. The correct answer is x is equal to \( 2c - \frac{2b}{3} \).